Effect of preservation time on the quality of frozen semen in indigenous rams (Bangladesh Journal of Animal Science, 2015)
The study was carried out to observe the effects of preservation time on the quality of frozen semen of indigenous rams. Semen was collected using AV once a week from 4 rams. Tris based with 10% egg yolk and 7% glycerol extender was used to extend and freezing the semen. Fresh semen was evaluated for volume, density, mass motility and concentration, and mean values were observed as 0.8±0.2ml, 3.0±0.3, 3.2±0.7, 3.9±0.7×109/ml, respectively. Significant difference (p